Gamification And GDLC (Game Development Life Cycle) Application For Designing The Sumbawa Folklore Game ”The Legend Of Tanjung Menangis (Crying Cape)” - Lailatul Husniah; Bayu Fajar Pratama; Hardianto Wibowo (Universitas Muhammadiyah Malang, 2018)
Sumbawa is popularly known as one of the regions in Indonesia, having a well- known folklore among the Sumbawa people, entitled the legend of Tanjung Menangis (Crying Cape). However, Tanjung Menangis is commonly recognized for its beauty than the stories contained. Therefore, a research is carried out by developing a game that is employed as a tool to introduce the story of Tanjung Menangis Legend as effort to preserve the original story of the mainland Sumbawa. The media game is chosen due to its favoured technology by children and adolescent as the target users of this research. This study applies Game Development Life Cycle (GDLC) method in the development stage which consists of several stages includinng: pre-production, production, testing, and post-production by adding an element of gamification. The game is tested on students at Labangka Elementary School in Sumbawa district in an age range of 10-15 years. After playing the game, the majority of respondents states that students gain knowledge about the Legend of Tanjung Menangis as reported from the results of the t- test with a probability value of 7.369x10-41, which is far below the value of α = 0.05. This result means that there was an increase in user knowledge of application. The test results also showed that all respondents agreed that the game of The Legend of Tanjung Menangis was used as one of the media used to introduce the story of the original Sumbawa people. In addition, the testing results as conducted with playtesting and gameflow test achieved good grades, with a range of values 4.5-4.81 of the seven elements tested, including: Concentration, Challenge, Player Skills, Control, Clear Goals, Feedback, and Immersion.